Workload of the Inpatient Nurses: What are the Affecting Factors? - Asjanti, Lidia; Irbantoro, Dolly; Rahmani R, Devita (Fakultas Kedokteran Universitas Brawijaya, 2021)
High nurse workload can impact the quality of hospital services. Nurses are the spearhead of the services, so they must obtain attention and be professionally managed to provide positive contributions to the advancement of the hospital. This study was conducted to describe the factors that influence the high workload of nurses in the Surgical and Internal Inpatient Installation (IRNA BDB) Baptis Batu Hospital. Qualitative and quantitative study methods with an explorative, descriptive approach were used. Determination of the root of the problem was using the fishbone diagram. Factors that influence the high workload of inpatient nurses are the number of nurses that do not meet the workload needs, placement of junior nurses and interns increases more workload for senior nurses, nurses carry out financial administrative tasks, blood sampling for laboratory examinations, and dispensing sterile preparations, as well as nurse call and bathroom facilities that are not supportive. In short, the causes of the high nurse workload are the lack of nurses, varied nurse qualities, non-nursing workloads, and less supportive facilities.